Improved Ability to Read Al-Qur'an Through the Tahfidz Al-Qur'an Mentoring Model - Sutiono Sutiono; Marliza Oktapiani; Syarifah Soraya (International Journal of Emerging Issues in Islamic Studies, 2023)
The Qur'an, as a guide for Muslims, has a positive influence on a person's psychology. In pursuing learning to read the Qur'an regularly and evaluating what has been understood, repetition and gradually learning according to its development can give the meaning of fluency and fluency. Mentoring models that suit the needs of students need to be considered. However, Tajwid, it has not been programmed in a structured manner. This study aims to determine the mentoring program and model that affects the ability to read the Qur'an at MTs Kafila Ibnu Mas'ud, East Jakarta. This research was conducted by case study (case study) using descriptive analysis method through a qualitative approach. The primary data sources are observation, interviews, and documentation with research samples, including school principals, student curriculum representatives, tahfiz teachers, and students of MTs Kafila Ibnu East Jakarta Mas'ud. This study's results indicate that the Al-Qur'an reading mentoring program at the Tahfiz program at MTs Kafila Ibnu Mas'ud East Jakarta was implemented by mapping students and dividing targets through the Regular Level, Mutawasith level and Mumayyazah level. The limitation of this research is the Tahfiz program in 2021/2022. The novelty of this research is that the program carried out by the school includes a structured mentoring program model that focuses on the school's vision and mission so that this program targets students to memorize three to ten Juz and focuses on the ability of teachers and qualifications to support students' abilities in achieving the tahfiz program.